Comparative Effect of Miosta-H and Bodifors Preparations on The Quality Indicators of Bull Beef - Bobomurodov, U.; Salimov, Yu. (American Journal of Biomedicine and Pharmacy, 2026)
This scientific article presents a veterinary and sanitary evaluation of the quality of meat obtained from bulls as a result of the effects of the biostimulants Miosta-H and Bodifors on the animal organism. When Miosta-H was administered to fattening bulls at an initial dose of 2.5 ml, followed by a repeated intramuscular injection into the neck region after 30 days, and the animals were slaughtered for meat 60 days after the beginning of the experiment, the organoleptic quality indicators of the meat were assessed using a 9-point scale. The experimental group scored 8.65 points, whereas the control group scored 8.20 points. In the case of Bodifors, the biostimulant was administered to experimental bulls at a dose of 8 ml, repeated four times at 14-day intervals. At the end of the experiment, the bulls were slaughtered, and the organoleptic quality indicators of the meat were evaluated at 8.6 points. Biochemical quality indicators of meat from bulls treated with Miosta-H showed a pH value of 5.9, a positive peroxidase reaction, and a clear filtrate in the formalin test. In bulls treated with Bodifors, the pH was 6.0, the peroxidase reaction was positive, and the formalin test filtrate was clear. In the control group, these indicators were pH 6.1, a positive peroxidase reaction, and a slightly clear filtrate. The dressing percentage of bulls treated with Miosta-H was 58%, while it was 57% in the Bodifors group and 55% in the control group. The results obtained from the experiments confirm that the use of Miosta-H and Bodifors preparations has a positive and effective impact on the veterinary and sanitary quality indicators of bull beef.